Endometrial expression of ERRβ and ERRγ: prognostic significance and clinical correlations in severe endometriosis - Wang, Zhenna; Guo, Sang; Xie, Yi; Tong, Yao; Qi, Wei; Wang, Zhenhong (Frontiers in Endocrinology, 2024)
Background: Endometriosis (EMs) results in approximately 50% of reproductive-age women facing infertility. Currently, no precise model is available to predict successful postoperative pregnancy. Methods: This study involved 81 patients with severe EMs (stages III and IV) and 38 controls with benign gynecological conditions, matched by age and BMI, diagnosis at Fujian Maternity and Child Health Hospital from January 2018 to December 2019. Relative expression levels of ERRβ and ERRγ mRNA in ectopic and ectopic endometrial tissues were measured using fluorescence quantitative PCR. Serum levels of ERRβ, ERRγ, and fertility-related hormones (AMH, FSH, LH, CA125) were assessed. Correlations were analyzed, and the predictive value of ERRγ for postoperative pregnancy was evaluated using a nomogram based on LASSO and multivariate logistic regression. Internal validation using bootstrapping techniques assessed the nomograms performance, including calibration and DCA. Results: ERRβ and ERRγ mRNA levels from ectopic tissues were significantly reduced in patients with severe EMs compared to controls. High serum CA125 correlated with increased ERRγ mRNA expression in ectopic tissues. ERRγ mRNA expression in ectopic endometrial tissues was negatively correlated with age, BMI, and FSH levels, and positively with AMH and LH/FSH ratio. ERRγ mRNA and FSH were significant predictors of postoperative pregnancy, with the nomogram model showing a Brier score of 0.175 and a consistency statistic of 0.811. Conclusions: ERRβ and ERRγ are downregulated in ectopic tissues from severe EMs. Elevated ERRγ mRNA expression and lower FSH levels are predictive factors for successful postoperative pregnancy.